Relationship among Sexual Knowledge, Sexual Attitudes, and Sexual Behavior of Junior High School Students in West Jakarta - Putra Brillian Djohan; Francisca Tjhay; Surilena Hasan; Nelly Tina Widjaja (Fakultas Kedokteran Universitas Brawijaya, 2021)
Lack of sexual knowledge and increasing negative sexual attitudes in Indonesia could lead to risky sexual behavior. This problem increases teenage pregnancy, sexually transmitted infections, and abortion among adolescents. This study aimed to determine the relationship between sexual knowledge and sexual attitudes towards sexual behavior among junior high school students in West Jakarta. This study was cross-sectional, conducted on 544 junior high school students in West Jakarta. Measuring instruments used were characteristic questionnaires, sexual knowledge questionnaires, sexual attitude questionnaires, and sexual behavior questionnaires. Data analysis was performed using bivariate (chi-square). This study shows 79.2% of the respondents had low sexual knowledge, 45.6% respondents had negative sexual behavior, and 48.2% respondents had risky sexual behavior. This study finds that most male respondents had low sexual knowledge (80.8%), low sexual attitude (56.8%), and â€œless-safeâ€ risky sexual behavior (60.0%), while â€œnot-safeâ€ risky sexual behavior (2.7%) was found higher in female respondents. Bivariate analysis shows a significant relationship between sexual knowledge (p=0.006; 95% OR=1.763 |95% CI=1.151-2.698) and sexual attitude (p=<0.001; OR=2.852 | 95% CI=2.012-4.043) towards sexual behavior. In conclusion, low sexual knowledge and negative sexual attitudes increase the risk of risky sexual behavior.